Case Study Of Jati Fishing Industries Sdn. Bhd. - Raja Yaacob, Raja Razali (2009)
The objective of this case study are to answer the questions above and to provide recommendations for JFI to move forward. It will examine and analyze the global and Malaysian fishing industry. It will also examine and analyze the approach taken by JFI in venturing into the fishing industry and positioning itself in the industry.